Aplikasi Hidroponik NFT pada Budidaya Pakcoy (Brassica rapa chinensis) - Wibowo, Sapto; Asriyanti S, Arum (Jurnal Penelitian Pertanian Terapan, 2013)
Nutrient Film Technique (NFT) is one of hydroponic system with the roots of plants put on a thin layer of water that resembles a film. Circulate the water and nutrients needed by plants. Movement of nutrient solution circulation but because of the encouragement of the pump, is also caused by the slope of the gutter pipes are used. Gutter pipe slope is getting steeper can cause plants to be difficult to stand up straight and nutrients are absorbed a bit because the flow is too fast. The slope of the gutter pipe that is too small can cause nutrient flow easily clogged because the flow is too slow. Therefore, in this study the slope of the NFT gutter pipe used was 1%, 3%, 5%, and 7%. The aim is to determine the effect of NFT gutter pipe slope on the growth and yield of pakcoy. Analysis used to determine whether there is difference in the growth and production of different crops on slopes is ANOVA (Analysis of variances) in one direction because there is only one independent variable, followed by a test of Honestly Significant Difference (HSD) at 5% significance level. The results show that there are differences in average growth and crop production pakcoy using different NFT gutter pipe. NFT gutter pipe slope the best effect on plant growth (number of leaves, plant height, and root length) and pakcoy crop production (weight of the plant) is on a slope of 5%, with the results for each crop is the average number of leaf 9.1 strands, the average plant height 18.4 cm, the average length of the roots of plants 41.5 cm, and an average weight of 34.49 g plant. Keywords: gutter pipe slope, NFT , pakcoy, growth, production